Speech Recognition with In-the-Ear and Behind-the-Ear Dual-Microphone Hearing Instruments - Pumford, John M.; Seewald, Richard C.; Scollie, Susan D.; Jenstad, Lorienne M. (Journal of the American Academy of Audiology, 2000)
The primary purpose of this study was to compare the overall listening benefit in diffuse noise provided by dual-microphone technology in an in-the-ear (ITE) hearing instrument to that provided by dual-microphone technology in a behind-the-ear (BTE) hearing instrument. Further, the study was designed to determine whether the use of the dual-microphone + the manufacturer's party response algorithm in the ITE and BTE hearing instruments provided listening benefit in diffuse noise over their respective omnidirectional microphone modes. Twenty-four adults with mild to moderately severe sensorineural hearing loss were evaluated while wearing binaural BTE and ITE hearing instruments. The results indicated that the dual-microphone + party response mode did provide significant benefit in diffuse noise for both the ITE (3.27 dB signal-to-noise ratio [SNR] improvement) and BTE (5.77 dB SNR improvement) hearing instruments relative to their respective conventional omnidirectional microphones. No significant difference in performance was found between the ITE and BTE hearing instruments when each device was in the dual-microphone + party response mode. It is concluded that the use of dual-microphone technology in both ITE and BTE hearing instruments can improve speech recognition in diffuse noise.Abbreviations: BTE = behind the ear, DI = Directivity Index, DSL [i/o] = desired sensation level input/output, HINT = Hearing in Noise Test, ITE = in the ear, KEMAR = Knowles electronic manikin for acoustic research, REAR = real-ear aided response, RECD = real-ear-to-coupler difference, RESR = real-ear saturation response, RTS = reception threshold for sentences, SC + a.R.T = super compression plus adaptive recovery time, SNR = signal-to-noise ratio
Keywords: Directional microphone; dual microphone; hearing instruments; omnidirectional microphone; signal-to-noise ratio; speech recognition